Apology in the Criminal Justice Setting: An Update - Carrie Petrucci (Oñati Socio-Legal Series)
Apology has many benefits to offenders and victims. The last 15 years have produced worthwhile quantitative and qualitative studies that have refined our understanding of apology, but have also identified the diversity in what can be said in apology and how it can be received. The apology literature in the last 15 years in social psychology, criminology, and criminal justice is examined, including two and three-way interaction effects and qualitative results that focus on the effectiveness of apology at the contextual and individual levels, and the important role that emotion can play. It is recommended that apology be implemented with a “less is more” approach for apology to be most effective for youth in juvenile justice; and that a venue is provided for a spontaneous/voluntary apology to occur, or a minimally prepared apology, using only broad prescriptions on how it ought to be carried out. By utilizing appropriate research strategies, knowledge about apology and its effectiveness in legal settings including juvenile justice can continue to build to determine what type of apology works best for whom under what circumstances.